2019
DOI: 10.15171/hpp.2019.29
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of problematic internet use disorder and associated risk factors and complications among Iranian university students: a national survey

Abstract: Background: Despite the growing epidemic of problematic Internet use (PIU), little information is available on PIU and related factors in Iran. Methods: This cross-sectional study was conducted on 4261 university students among 13 universities throughout the country in 2017. The data collection tool included demographic characteristics, the status of using the Internet, social media, computer games, tobacco, alcohol, and illicit drugs, suicide ideation and attempt, and unprotected sex. PIU was measured using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 36 publications
3
32
0
3
Order By: Relevance
“…Especialistas têm endossado que o envolvimento excessivo em tais atividades online durante a pandemia pode se tornar difícil de controlar e gradativamente adquirir centralidade na vida daquelas pessoas que estejam vulneráveis, desenvolvendo a sintomatologia de comportamentos aditivos [40][41][42][43] . Para além dos efeitos do uso intensivo de internet na saúde mental e na perda de qualidade de vida, amplamente reportados 36,44,45 , há ainda de se considerar os impactos na diminuição das atividades físicas e mudanças prejudiciais nos hábitos alimentares, que consequentemente contribuem para agravar condições de saúde como obesidade e diabetes 46,47 .…”
Section: Variáveisunclassified
“…Especialistas têm endossado que o envolvimento excessivo em tais atividades online durante a pandemia pode se tornar difícil de controlar e gradativamente adquirir centralidade na vida daquelas pessoas que estejam vulneráveis, desenvolvendo a sintomatologia de comportamentos aditivos [40][41][42][43] . Para além dos efeitos do uso intensivo de internet na saúde mental e na perda de qualidade de vida, amplamente reportados 36,44,45 , há ainda de se considerar os impactos na diminuição das atividades físicas e mudanças prejudiciais nos hábitos alimentares, que consequentemente contribuem para agravar condições de saúde como obesidade e diabetes 46,47 .…”
Section: Variáveisunclassified
“…The prevalence of CUD is 4.4% among those aged 18–29 years, according to the Diagnostic and Statistical Manual of Mental Disorders, 5th Edition (DSM-5; American Psychiatric Association, 2013 ), making it the most prevalent illicit/non-medical drug disorder in University students. In a study conducted in Iran on 4261 university students, the prevalence of PIU was estimated at 27.3% ( Poorolajal et al, 2019 ). Furthermore, many studies have shown the relationship between insomnia ( Shadzi, Salehi, & Vardanjani, 2020 ), impulse control disorders ( Mazhari, 2012 ), poor general health ( Poorolajal et al, 2019 ), anxiety ( Hashemi et al, 2020 ), and PIU among the Iranian population.…”
Section: Introductionmentioning
confidence: 99%
“…In a study conducted in Iran on 4261 university students, the prevalence of PIU was estimated at 27.3% ( Poorolajal et al, 2019 ). Furthermore, many studies have shown the relationship between insomnia ( Shadzi, Salehi, & Vardanjani, 2020 ), impulse control disorders ( Mazhari, 2012 ), poor general health ( Poorolajal et al, 2019 ), anxiety ( Hashemi et al, 2020 ), and PIU among the Iranian population. In a meta -analysis, the prevalence of CUD among Iranian college students was 2%–3% ( Nazarzadeh et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…According to a study by Dastani et al (2015) in Gonabad University of Medical Sciences, the main purpose of social media usage in students are communication with old friends, nding new friends and entertainment (14). According to a study by Pouralajel et al, The higher the use of the Internet, the lower the students' grades, and in addition, better students' grades, was associated with less social media use (10).…”
Section: Introductionmentioning
confidence: 99%
“…Excessive use of social media can lead to several undesirable effects, including: anxiety, stress and adverse effects on school performance (9). Internet addiction can also be associated with psychological problems such as depression and drug abuse, suicide and nomophobia (10,11).Reasons for such interest in using Internet is due to its easy access, widespread use, low cost, multimedia sharing feature and lack of need for special skills (12). According to several studies conducted in Iran, since students are often away from their families after admission to the University, in order to stay in touch with their friends and families, students tend to use social media which makes the effects of social media perfectly visible in this period (13).…”
Section: Introductionmentioning
confidence: 99%